Ancient Rome - James, Simon, 1957- (New York Alfred A. Knopf, 1990)
A photo essay documenting ancient Rome and the people who lived there as revealed through the many artifacts they left behind, including shields, swords, tools, toys, cosmetics, and jewelry.
Include Index and Colour Illustration
Keywords: Rome (Empire) -- Antiquities -- Civilization